The comparative characteristic of pheno- and genotypical signs in neonates with atresia of duodenum and other parts of the small intestine - O. K. Botvin'yev; A. V. Eremeeva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Analysis of phenotypical and genotypical signs in neonates with atresia of duodenum and other parts of the small intestine.Material and methods. The comparative characteristic of phenotypical and genotypical signs in 68 neonates with atresia of duodenum (the first group) and 67 children with atresia of other parts of the small intestine (the second group) was carried out. Main anthropometric parameters were investigated at birth (body weight, body height, circumference of head and chest), concomitant malformations, genic frequencies and phenotypical combinations of ABО and rhesus blood groups systems.Results. For these patients intra-uterine development disorders are typical, manifesting by decrease of all anthropometric scores, presence of various hypoplastic malformations of other organs and systems. The spectrum and location of congenital malformations in studied groups was different.Conclusions. The atresia of duodenum and other parts of the small intestine has polygenic mode of inheritance. Disorders of intra-uterine development are typical for investigated patients. The spectrum and localization of congenital malformations in children with atresia of duodenum and atresia of other regions of the small intestine is different.